2021
DOI: 10.2298/tsci2102517h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fabric surface’s cleanliness on its moisture/air permeability

Abstract: A fabric?s moisture/air permeability is a main factor for the fabric design for advanced applications, and no theoretical model was available in literature for an optimal permeability. In this paper, we use the capillary-like effect to elucidate the permeability property, and the effect of nano/micro particles on the fabric?s surface on the permeability is studied by the geometric potential theory. Our theoretical analysis shows that an unclean surface gives a negative impact on the permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The thermal properties are basically consistent with PA and the carbon residue content was about 70%, which thereby effectively inhibits or slows down the combustion degree. This study provides a method for flame-retardant and wrinkle resistant finishing of fabrics, which can be mathematically treated [16][17][18]. The theoretical analysis will be carried out in Part 2 of this series of publications, where a mathematical model will be established.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal properties are basically consistent with PA and the carbon residue content was about 70%, which thereby effectively inhibits or slows down the combustion degree. This study provides a method for flame-retardant and wrinkle resistant finishing of fabrics, which can be mathematically treated [16][17][18]. The theoretical analysis will be carried out in Part 2 of this series of publications, where a mathematical model will be established.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2021 ), friction property ( Cao et al, 2021 ; Bains et al, 2020 ), and reflection property ( Selkowitz 2021 ). According to the geometric potential theory ( Peng and He, 2020 ; Han and He, 2021 ), a nano-scale surface can produce high geometric potential. It was reported that Fangzhu’s nano-scale surface can collect water molecules from the air ( He and El-Dib, 2021 ; Wu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, various devices have been developed for energy harvesting, such as the nanofluids (He and Elazem, 2022), the spring-pendulum systems (Wu et al, 2018;He et al, 2022a), and the lowfrequency vibration systems (Zhang and Cai., 2012;He C.-H. et al, 2021;. In addition to the abovementioned methods, the nanotechnology for solar energy harvesting (Satharasinghe et al, 2020) is totally new and is quite promising.…”
Section: Introductionmentioning
confidence: 99%
“…In the drafting zone, the fiber bundles as a whole akin to cylinder cross with the bottom pin consisting of several cylindrical surfaces. In the case of contact between two crossed cylinders, the Jonson–Kendall–Roberts (JKR) model 2527 is suitable to measure the friction force at the point of contact by considering the adhesive forces between surfaces. 28 Based on the JKR model, the contact radius a , when fiber bundles (R 1 ) and bottom pin (R 2 ) are compressed together under the applied load, is expressed as: where E is the elastic modulus, W 12 is the work of adhesion for two surfaces, N is the applied load and R=R1R2/(R1+R2).…”
Section: The Novel Drafting Devicementioning
confidence: 99%